Path to National Champions: Transforming Support Policies for Small- and Medium-Sized Enterprises (SMEs) - Minho Kim (Korea Development Institute (KDI), 2024)
South Korea's 'national champion policy,' designed to foster global enterprises, has yet to deliver measurable outcomes in sales and productivity, suggesting inefficiencies in resource allocation linked to 'the risk of picking winners.' Accordingly, the incentive structure of growth policies for Small- and Medium-Sized Enterprises (SMEs) needs an operational shift, moving away from conventional subsidy assistance toward a bespoke model that integrates private investment, consulting, and networks to address their business challenges collaboratively. Furthermore, in order to enhance policy accountability and effectiveness, it is crucial to consolidate support details and performance outcomes while ensuring transparency through public disclosure.
Keywords: 330